PENGARUH PENDAPATAN ASLI DAERAH (PAD) DAN DANA ALOKASI UMUM (DAU) TERHADAP STRUKTUR BELANJA DAERAH (Studi Pada Pemerintah Kabupaten/Kota di Jawa Timur) - Pipit Budiarti; Helmy Adam (Jurnal Ilmiah Mahasiswa FEB, 2013)
The aim of this study is to examine the factors of local revenues which predominantly affecting the structure of Regional Expense Allocation in percent. The dominant factors of Regional Expense Allocation used in this study consist of Local Own-source Revenue(PAD) and General Allocation Fund(DAU). The resources of this studybased from The Report of Local government budget(APBD)from 2010 to 2013 in 29 districs and 9 cities in East Java as its population. The research usedmethod by taking and describing the entire populationby multiple linear regression analysis asits tool. The results showed that PAD tested has a significant effect on the structure of Regional Expensein percent.The positiveeffects of DAUshowed on structureof Regional Expense Allocationwhich consist of indirect expenditures, operatingexpenditures, capital expenditures, unforeseen expenditures, and transferexpenditures percentation.Keywords: Local Own-source Revenue( PAD), General Allocation Fund (DAU),The Regional Expense Structure